Postsurgical Alveolar Bone Graft Patients: Elaboration and Application of a Data-Gathering Instrument for Nutrition and Nursing - Beluci, Marli Luiz; Barros, Suely Prieto de; Borgo, Hilton Coimbra; Fontes, Cassiana Mendes Bertoncello [UNESP]; Arena, Eliane Petean (Alliance Communications Group Division Allen Press, 2014)
Objectives: To relate nutritional status with food acceptance by patients undergoing alveolar bone grafting and to elaborate an interdisciplinary instrument for data collection, involving nutrition and nursing teams.Design/Intervention: A prospective, longitudinal, and comparative study with a quantitative approach was conducted in a tertiary institutional hospital. The nutritional anthropometric evaluation was performed one day before surgery (M1) and at hospital discharge (M2), by measuring body mass index (BMI), triceps skinfold thickness (TST), subscapular skinfold thickness (SST), and arm muscle circumference (AMC). The interdisciplinary instrument for data collection was used.Patients: The sample comprised 150 patients, aged 10 to 20 years, of both genders, who agreed to participate in this study.Results: Most of patients were well-nourished during the study. There was correlation between BMI and Sigma TST + SST at M1 and M2 (P < .0001) and between BMI and AMC (P < .0001). Concerning food acceptance, 145 patients had adequate intake and 5 did not. Comparisons between the groups of patients revealed decreases in values for BMI, Sigma TST + SST, and AMC from -0.37, 0.0, and 0.3, respectively, at M1 to -0.71, -3.0, and 0.0, respectively, at M2. BMI and AMC showed similar decreases in both groups.Conclusions: The interdisciplinary instrument was useful and appropriate for associating nutritional status with food acceptance, adding value for teamwork.
Keywords: nutrition assessment; anthropometry; nurse-patient relations